2018
DOI: 10.1186/s13018-018-0810-5
|View full text |Cite
|
Sign up to set email alerts
|

Is a patient-specific drill template via a cortical bone trajectory safe in cervical anterior transpedicular insertion?

Abstract: BackgroundThis study aimed to develop patient-specific drill templates by computer numerical control or three-dimensional printing via two cortical bone trajectories (CBTs) and to evaluate their efficacies and accuracies in cervical anterior transpedicular insertion.MethodsPreoperative CT images of 20 cadaveric cervical vertebrae (C3–C7) were obtained. After image processing, patient-specific drill templates were randomly assigned to be constructed via two CBTs (CBT0 and CBT0.7) and manufactured by two methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…The accuracy of PDTs in facilitating C2TOPI is of vital importance. In the present study, we calculated the absolute value of the deviations from the centroids between the preoperative designs and postoperative measurements, which had been used in our previous studies [2527] to show the actual deviations. Our study showed that the absolute deviations in the axial plane (0.79 ± 0.64 mm) and the sagittal plane (0.96 ± 0.51 mm) in the PDT group might be within an acceptable range for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of PDTs in facilitating C2TOPI is of vital importance. In the present study, we calculated the absolute value of the deviations from the centroids between the preoperative designs and postoperative measurements, which had been used in our previous studies [2527] to show the actual deviations. Our study showed that the absolute deviations in the axial plane (0.79 ± 0.64 mm) and the sagittal plane (0.96 ± 0.51 mm) in the PDT group might be within an acceptable range for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“… 2018 Peng P et al. [ 76 ] J Orthop Surg Res 4 cadaver CBT screw fixation Bio-safe drill templates can facilitate cervical anterior transpedicular insertion with good feasibility and accuracy. 2018 Krämer M et al.…”
Section: Basic Types and Clinical Applications Of Orthopedic 3d Print...mentioning
confidence: 99%
“…On this basis, Peng et al. [ 76 ] developed a template for guiding cortical bone trajectory screws. It successfully improved the success rate of screw placement and reduced intraoperative complications.…”
Section: Basic Types and Clinical Applications Of Orthopedic 3d Print...mentioning
confidence: 99%
“…Alternatively, a guidance system such as O-arm-based three-dimensional (3D) navigation, 3D model, navigation templates, Doppler donography, robotic guidance system, [7][8][9][10][11][12] or augmented reality-based navigation [13 14] is needed to prevent placement failure. The use of these resources is limited because of their high cost and steep associated learning curve however, and they cannot be widely applied in all kinds of hospitals.…”
Section: Introductionmentioning
confidence: 99%